Profiled rotary dresser with controlled size and distribution of abrasive grits: Performance assessment. Issue 1 (2019) - Spampinato, Alessio; Axinte, Dragos; Butler-Smith, Paul
Abstract: This paper reports on a novel proprietary profiled rotary dresser which, in contrast with conventional tools, enables a controlled arrangement of geometrically defined abrasives over complex profiles. Output forces and abrasives' wear were investigated during dressing and grinding tests. This showed a significant reduction in radial dressing forces (˜37%) and volumetric loss of material per grit (˜21%) when compared with conventional tools, together with low grinding forces and workpiece surface roughness variability for different wear conditions. The novel dresser proves the ability to obtain uniform wear rates along complex profiles, while allowing abrasive segment replacement to restore the dressing conditions.